Real-time Score Generation for Extensible Open Forms. - Kim-Boyle, David (Contemporary Music Review, 2010)
While composers have often employed graphic scores and other extended notation systems to explore open-form, collaborative, and aleatoric musical processes, the notational forms themselves have traditionally been presented to performers through fixed, paper-based media. In this article, several compositions by the author are described in which dynamic scores are generated in real-time during a performance and projected for the performer to read from a laptop screen or video display. The processes used to generate such scores will be described in detail and a number of the practical and musical challenges presented by the notational procedures employed will also be addressed.